An extended Shine–Dalgarno sequence in mRNA functionally bypasses a vital defect in initiator tRNA - Shetty, Sunil (National Academy of Sciences, 2014)
Initiator tRNAs are special in their direct binding to the ribosomal P-site due to the hallmark occurrence of the three consecutive G-C base pairs (3GC pairs) in their anticodon stems. How the 3GC pairs function in this role, has remained unsolved. We show that mutations in either the mRNA or 16S rRNA leading to extended interaction between the Shine–Dalgarno (SD) and anti-SD sequences compensate for the vital need of the 3GC pairs in tRNA(fMet) for its function in Escherichia coli. In vivo, the 3GC mutant tRNA(fMet) occurred less abundantly in 70S ribosomes but normally on 30S subunits. However, the extended SD:anti-SD interaction increased its occurrence in 70S ribosomes. We propose that the 3GC pairs play a critical role in tRNA(fMet) retention in ribosome during the conformational changes that mark the transition of 30S preinitiation complex into elongation competent 70S complex. Furthermore, treating cells with kasugamycin, decreasing ribosome recycling factor (RRF) activity or increasing initiation factor 2 (IF2) levels enhanced initiation with the 3GC mutant tRNA(fMet), suggesting that the 70S mode of initiation is less dependent on the 3GC pairs in tRNA(fMet).